2019
DOI: 10.1002/pon.5238
|View full text |Cite
|
Sign up to set email alerts
|

We are in this together — Aren't we? Congruence of common dyadic coping and psychological distress of couples facing breast cancer

Abstract: Objectives Breast cancer (BC) can be understood as a we‐disease, which affects a couple as a unit and requires coping as a unit (eg, common dyadic coping, CDC). However, partners can be incongruent in their perceptions of CDC, for example, because of misunderstandings and lack of mutuality or conflict, which may likely be associated with greater distress. Thus, this paper examines the effect of CDC congruence on individual psychological distress in cancer patients and their partners. Methods Seventy mixed‐sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 37 publications
4
33
1
Order By: Relevance
“…In our study, women who perceived their partner as more interested and actively involved in the management of endometriosis (for instance by accompanying them to the medical visits) reported greater relational satisfaction and better dyadic coping. Taken together, these findings highlighted the importance of coping strategies based on mutuality and we-ness ("we are in this together" [47]), which seem to be particularly helpful for women coping with different types of stressors (such as breast cancer [49]), as recently underlined by Rusu et al [50].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In our study, women who perceived their partner as more interested and actively involved in the management of endometriosis (for instance by accompanying them to the medical visits) reported greater relational satisfaction and better dyadic coping. Taken together, these findings highlighted the importance of coping strategies based on mutuality and we-ness ("we are in this together" [47]), which seem to be particularly helpful for women coping with different types of stressors (such as breast cancer [49]), as recently underlined by Rusu et al [50].…”
Section: Discussionmentioning
confidence: 55%
“…Specifically, our findings highlighted the correlation between positive dyadic coping -especially common dyadic coping (which occurs when both partners make efforts to cope together with a shared stressor) -and the mental health of women with endometriosis. The role played by common dyadic coping strategies in the context of clinical samples (including couples coping with diabetes, cancer, or psychological disorders such as depression) and its positive outcomes for couples, in terms of decreased distress and greater relational satisfaction, have been highlighted in previous studies [26,[45][46][47]. On the other hand, our study confirmed that negative dyadic coping (which entails responding with hostility, sarcasm, distancing, superficiality, or ambivalence to the partner's signals of stress) is associated with poorer psychological health in people with chronic illness, as previously demonstrated by other authors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Different areas of relationship characterize the dyadic process of psychological adaptation to breast cancer. The deployment of shared coping strategies, defined as joining forces to face the problem, and the availability of instrumental and emotional support have been frequently mentioned in the studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In regard to coping strategies, couples who adopt common dyadic coping strategies, consisting of the attempt of one member of the dyad to reduce the stress perceived by the other member and as a common effort to cope with the situation, report less psychological distress [ 38 ] and high levels of adaptation to the pathology [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The deployment of shared coping strategies, defined as joining forces to face the problem, and the availability of instrumental and emotional support have been frequently mentioned in the studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In regard to coping strategies, couples who adopt common dyadic coping strategies, consisting of the attempt of one member of the dyad to reduce the stress perceived by the other member and as a common effort to cope with the situation, report less psychological distress [ 38 ] and high levels of adaptation to the pathology [ 32 ]. In this context, a crucial role is played by the merging strengths [ 33 ] that are defined as the capability of the couple to join efforts and collaborate to face the challenges of the diagnosis (e.g., walking together, searching for information and support networks, trusting together, staying together).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of chronic health impairments, systematic reviews similarly show that conjoint dyadic coping is consistently associated with good relationship functioning (Traa et al, 2015). In couples coping with the wife's breast cancer, higher CDC was associated with higher relationship quality and fewer depressive symptoms in both patients and partners (Rottmann et al, 2015) and with lower psychological distress in partners (Meier et al, 2019). In couples coping with diabetes, CDC was related to patients' adherence to dietary and exercise regimens which is vital to avoid serious complications (Johnson et al, 2013).…”
Section: We-stress and Conjoint Forms Of Dyadic Copingmentioning
confidence: 99%